A cortesia na conversação informal - Silva, Ana Cristina Tarelo da (2016)
This work is part of field studies on the analysis of conversation and is he result of research that aimed to reflect on the characteristics of courtly accomplishments in informal conversation and more particularly on the phenomenon called discourtesy feigned (BRIZ, 2014) ( ALBA-JUEZ, 2008), combining the socio-pragmatic analysis to the apparatus of the theory of faces. he research in question had as its object conversations in Facebook social network environment. To perform the analyzes were adopted as theoretical pparatus the concepts relating to Conversation Analysis (Marcuschi, 1999); (Kerbrat-Orecchioni, 2006), the theory Threatering Face Acts-FTAs (Brown & LEVINSON, 2014 [1978]), extended the concepts of the Flattering Face Acts-FFAs (KERBRA-Orecchioni 1986, 2006), together with the in studies on pragmatic and complimentary variation and attenuation approach cultures (BRIZ, 2014, 2013, 2010, 2006)